The Antimicrobial Effect of Melissa officinalis L. Essential Oil on Vibrio parahaemolyticus: Insights Based on the Cell Membrane and External Structure - Yu, Huijie; Pei, Juxin; Qiu, Weiqiang; Mei, Jun; Xie, Jing (Frontiers in Microbiology, 2022)
The study was to evaluate the antimicrobial impacts on Melissa officinalis L. essential oil (MOEO) against Vibrio parahaemolyticus. The minimum inhibitory concentration (MIC) of MOEO on Vibrio parahaemolyticus was 1 μL·mL-1. The kill-time curve exhibited that MOEO had a good antimicrobial activity. The analysis of cellular ingredients leakage and cell viability illustrated that MOEO has destruction to the morphology of the cell membrane. The damage to the membrane integrity by MOEO has been confirmed by transmission and scanning electron microscopy, obvious morphological and ultrastructural changes were observed in the treated bacterial cells. The MOEO at 0.5 μL·mL-1 can inhibit the biofilm formation, biofilm motility, and extracellular polysaccharide production. Meanwhile, the qPCR results exhibited MOEO inhibited the expression of virulence genes. The findings showed that MOEO exerted its antimicrobial effect mainly by destorying the membrane, which indicated its potential as a natural food preservative.